Presenting the AfriArch Isotopic Database. (8th December 2022) - Goldstein, Steven; Hixon, Sean; Scott, Erin; Wolfhagen, Jesse; Iminjili, Victor; Janzen, Anneke; Chritz, Kendra; Sawchuk, Elizabeth; Ndiema, Emmanuel; Sealy, Judith C.; Stone, Abigail; Zoeller, Gretchen; et al.
AfriArch is an archaeological and paleoenvironmental data community designed to integrate datasets related to human-environmental interactions in Holocene Africa. Here we present a dataset of bioarchaeological stable isotope (C/N/O) and radiocarbon measurements from African archaeological sites spanning the Holocene. Modern measurements, when reported together with archaeological data in original publications, are also included. The dataset consists of 5568 entries and covers the entirety of Africa, though most isotopic research has been concentrated in southern Africa. The AfriArch isotopic dataset can be used in paleodietary, paleodemography, paleoclimatic, and paleoenvironmental studies. It can also be employed to highlight data gaps across space and time and set future research agendas.